Word-Wall Technique in Improving Students’ Vocabulary Mastery at the first Grade of SMPN 4 Kajuara Kabupaten Bone - Misrawati Misrawati; Sitti Nurjannah; Muthmainnah Mursidin (STKIP Andi Matappa Pangkep, 2020)
This research aims to know (1) whether the use of word wall technique is able to improve students’ vocabulary mastery, (2) the students’ interest to learn vocabulary by using word wall technique. This research was conducted at SMPN 4 Kajuara Kabupaten Bone academic year 2017-2018. The subject of this research consisted of 52 students of first grade. The design of the research was quasi-experimental design where the research used two group, they were experimental group and control group. There were 2 classes as a sample namely VII-A as experimental group (taught by word wall) with the total number of 26 students and VII-B as control group (without word wall) with the total number of 26 students. The researcher administered pre-test and post-test to both groups. The result of data shows that there an improvement and interest of using word wall technique toward the students’ vocabulary mastery. Thre percentage of students’ pre-test of experimental group was 19.34 and the score of post-test was 41.74. Therefore, the alternative hypothesis (Ha) of this research is accepted. It means that the use of ward wall technique improves students’ vocabulary mastery at the first grade of SMPN 4 Kajuara Kabupaten Bone.Penelitian ini bertujuan untuk mengetahui (1) apakah penggunaan teknik dinding kata mampu meningktkan penguasaan kosakata siswa, (2) ketertarikan siswa untuk belajar kosakata dengan dinding kata. Penelitian ini telah diadakan di SMPN 4 Kajuara Kabupaten Bone tahun pelajaran 2017/2018. Pokok persoalan pada penelitian ini terdiri dari 52 siswa kelas satu. Bentuk penelitian adalah berbentuk quasi-experimental dimana penelitian menggunakan dua kelompok, yaitu kelompok experimen dan kelompok control. Ada dua kelas sebagai sampel yakni, VII A sebagai kelompok ekperimen (mengajar dengan dinding kata) dengan jumlah 26 siswa dan VII B sebagai kelompok kontrol (tanpa dinding kata) dengan jumlah 26 siswa. Peneliti memberikan pre-test and post-test untuk kedua kelompok. Hasil dari data menujukkan ada peningkatan dan ketertarikan dengan menggunakan teknik didnding kata terhadap peningkatan kosakata siswa. Persentasi skor siswa sebeum diajarkan dengan menggunakan teknik dnding kata adalah 19.34% dan setelah mengajar dengan teknik dinding kata adalah 41.76%. Oleh karena itu, hipotesis altenatif (Ha) untuk penelitian ini diterima. Itu berarti bahwa penggunaan teknik dinding kata meningkatkan penguasaan kosakata siswa di kelas satu SMPN 4 Kajauara Kabupaten Bone.